The association between flooring materials and childhood asthma: A prospective birth cohort in the Japan Environment and Children's Study. - Hiroyoshi Iwata; Atsuko Ikeda; Mariko Itoh; Sachiko Itoh; Rahel Mesfin Ketema; Naomi Tamura; Chihiro Miyashita; Takeshi Yamaguchi; Keiko Yamazaki; Rieko Yamamoto; Maki Tojo; Yasuaki Saijo; et al. (PLoS ONE, 2024)
Background Childhood asthma is known to be affected by a range of factors, including conditions in the indoor environment. While flooring material influences indoor air conditions, the potential association between flooring materials and childhood asthma remains poorly understood in Japan. Objective The present study aims to assess the association between childhood asthma incidence and the primary flooring material with the ongoing prospective nationwide birth cohort data of the Japan Environment and Children's Study (JECS). Methods The JECS gathered data on mothers and children through 15 Regional Centres across Japan. The present study assessed flooring materials used in the home and asthma incidence at age four among children born between 2011 and 2014. We implemented logistic regressions, setting asthma incidence among the children as the outcome and home floor type as the exposure. Additional analyses were conducted, stratifying the home's age as a proxy for tatami age, to assess whether the potential effect of tatami flooring on asthma risk is influenced by its age. Results The present study included total of 75,629 infants. For tatami flooring, the main multivariable regression and additional sub-group regression for homes over ten years old produced odds ratios of 1.09; 95% Confidence Interval (CI) [1.01-1.17] and 1.10; 95% CI [1.00-1.21] compared with flooring, respectively. Conclusion These results imply that exposure to tatami flooring, particularly in older homes, may be associated with childhood asthma incidence. Moreover, our study highlights the importance of evaluating the relationship between regional and cultural differences between asthma and flooring materials.